2014
DOI: 10.1002/ijc.29205
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation array analyses identified breast cancer‐associated HYAL2 methylation in peripheral blood

Abstract: Breast cancer (BC) is the leading cause of cancer-related mortality in women worldwide. Changes in DNA methylation in peripheral blood could be associated with malignancy at early stage. However, the BC-associated DNA methylation signatures in peripheral blood were largely unknown. Here, we performed a genome-wide methylation screening and identified a BC-associated differentially methylated CpG site cg27091787 in the hyaluronoglucosaminidase 2 gene (HYAL2) (discovery round with 72 BC case and 24 controls: p 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 50 publications
3
64
0
1
Order By: Relevance
“…After excluding non-eligible articles (see Fig. 1a and Additional file 1: Supplementary materials), 45 articles could be included in this review, including 26 articles used DNA isolated from whole blood [1421, 2441], two articles used DNA isolated from both whole blood and plasma [42, 43], six articles used DNA isolated from plasma [4449], and 11 articles used DNA isolated from serum [5060] (Table 1). For the studies that used serum or plasma as DNA source, four of them used two centrifugation steps to get serum or plasma [42, 45, 47, 48] and the rest used one centrifugation step or sample processing procedures are not available (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding non-eligible articles (see Fig. 1a and Additional file 1: Supplementary materials), 45 articles could be included in this review, including 26 articles used DNA isolated from whole blood [1421, 2441], two articles used DNA isolated from both whole blood and plasma [42, 43], six articles used DNA isolated from plasma [4449], and 11 articles used DNA isolated from serum [5060] (Table 1). For the studies that used serum or plasma as DNA source, four of them used two centrifugation steps to get serum or plasma [42, 45, 47, 48] and the rest used one centrifugation step or sample processing procedures are not available (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al [21] showed that reduced methylation levels of the HYAL2 gene were significantly associated with increased BC risk. Specifically, women in the highest quartile of HYAL2 methylation were reported to have a 41.47-fold (cohort I) and a 132.98-fold (cohort II) increased BC risk, compared with women in the lowest quartile (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many biomarker genes have been proposed and evaluated; nevertheless, in the absence of a unique biomarker having sufficient specificity and sensitivity, a panel of multiple genes should be used [121][122][123] . Modifications of cancer-related genes could occur at genetic and epigenetic levels, affecting DNA repair.…”
Section: Clinical and Therapeutic Implications Of Intra-tumor Heterogmentioning
confidence: 99%
“…To validate genome-wide DNA methylation profiles during multistage hepatocarcinogenesis, Ammerpohl et al [105] revealed that the methylation status have changed gradually from normal to cirrhosis and further to HCC using a methylation array. Nagashiro et al [106] established criteria for carcinogenetic risk estimation based on DNA methylation array profiling to compare samples of noncancerous liver tissue obtained from HCC patients with normal liver tissue samples.…”
Section: Applications Of Microarraysmentioning
confidence: 99%